How are education and research affected by regional development? - Rédei, Mária (REGIONAL AND BUSINESS STUDIES, 2011)
This article will discuss how education activity is combined with research in a transition period. The preliminary point of thinking is that the European Higher Education Area (EHEA) and European Research Area (ERA) are two pillars of the knowledge driven society, yet both of them are undergoing a troubled transition period. The manufacturing industry in Hungary has undergone restructuring. In consequence of this, the main sectors have begun operating by high added value activities. The relocation of industry and rapid development of international services in a low tax zone has raised demand for internationally experienced skill sources. Why is domestic education unable to feed this demand? How can national research and education be integrated more usefully? With the creation of a permeable border, both the transnational economy and the national experience were contaminated. Cross-border mobility is one element of internationalization. The author will raise some points related to the Hungarian situation on the basis of the „Salzburg Principles” for doctoral programmes. The main topic of this paper is how spatial restructuring has linked education output and technological relay. The presentation closes with some comparative recommendations on the trend experience. One such recommendation would be to integrate education and industry. This would provide more complementary skills and skilled workers who could in turn facilitate the growth of an integrated training and business strategy that would provide funds for both education and research in relevant fields. European and national funding rank the strategically and regionally operative priorities of development support from the top down, but project collaboration should be from the bottom up. There is a critical discrepancy between available funding and institutional and regional demand. The mutual benefit platform is missing.Keywords: transition, human resources, relocation, mobility